Transfer-enhanced cathode with noncorrosive inorganic-based composite additive for durable proton exchange membrane fuel cells - Lim, Katie Heeyum; Hwang, Jungsoo; Kim, Ohsub; Kim, Jihyun; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Lee, So Young; Yoon, Young-Gi; Kim, Tae-Young; Jung, Chi-Young; et al. (Elsevier BV, 2025)
Conventional cathodes of proton exchange membrane fuel cells (PEMFCs) composed of two components, Pt/C catalyst and ionomer, are cautiously fabricated to achieve efficient electron, ion, and mass transfer through the electrode. However, the degradation of the cathode structure due to carbon support oxidation limits the longterm operation of PEMFCs by interrupting gas transfer through the deformed electrode. This carbon corrosion problem is often addressed by replacing carbon with other catalyst-supporting materials, albeit with limited effects. Herein, we report a new cathode design that incorporates a noncorrosive additive as a third component into traditional PEMFC systems to mitigate cathode degradation, thereby enhancing PEMFC performance and durability. The noncorrosive additive improves PEMFC durability by more than three times compared to fuel cells without the additive in accelerated stress tests (ASTs). Through this simple process, the porous cathode structure maintains its integrity even under severe carbon corrosion, unlike conventional cathodes, thereby ensuring sustained transfer pathways for ions and gas fuels throughout the electrode. Moreover, the initial PEMFC performance increases by 13.6 %, attributed to the intensified porous networks in this new cathode design.